An Implementation of Comment Insertion Problem for Game Programming Study in Python Programming Learning Assistant System - Fujiwara, Haruya; Funabiki, Nobuo; Kao, Wen-Chung; Lee, Yi-Fang (IEEE International Conference on Consumer Electronics-China (Online), 2025)
Nowadays, Python programming has become an essential subject in universities and vocational schools because of its numerous advantages of rich libraries, short coding, and simple structure. Python has been widely adopted in various applications including AI, web systems, and games. Unfortunately, due to limitations in curriculum and teachers, Python programming courses are not sufficiently offered in schools, which will make an efficient self-study tool be in strong demands. Python programming learning assistant system (PyPLAS) has been developed to assist step-by-step self-learning of novice students, offering several types of exercise problems that have different learning goals. However, PyPLAS does not support game programming by Python, although it is suitable to study both logic programming and graphical user interface (GUI) programming at the same time. In this paper, we implement a comment insertion problem (CIP) for game programming study using Pygame library in PyPLAS. A CIP instance asks to fill in each blank in the source code for a game by selecting the proper comment among the given candidates. It is designed for novices to understand the structure of a game code composed of logics and GUI procedures. As a preliminary evaluation, we generated two CIP instances using simple game codes and assigned them to students in our laboratory. The questionnaire result confirmed the effectiveness.